Pengembangan Kreativitas Anak Tk Melalui Teknik Mewarnai Sejak Dini Dan Pengenalan Ikon Sederhana Pada Anak Pra-Remaja - Laura Zalfatika Azzahra; Shaneabel Azrya Utomo; Vincentius Alvin Resandy; Evelyne Henny Lukitasari (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
The increasing creativity and conceptual knowledge has a very important role in the development of children at an early and pre-teenager age. This research aims to identify the impact of developing the creativity of Muslimat Brajan Kindergarten children through the technique of coloring pictures and introducing icons in pre-teen children. The approach used includes the use of coloring pictures activities designed for kindergarten children and icon recognition sessions designed to introduce basic concepts interactively to pre-teen children. The results show that the use of focused coloring techniques and interactive introduction of icons makes a significant contribution to increasing the creativity of kindergarten children. For pre-teen children,aimed for their understanding of basic icons in the general scope. Coloring picture activities provide a platform for creative expression for children, while the introduction of icons opens up their insight into values, objects and living beings.